2009
DOI: 10.1111/j.1365-2109.2008.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of four anaesthetics on biochemical blood profiles of perch

Abstract: This study investigated the feasibility of using clove oil, 2-phenoxyethanol, or Propiscin as an alternative to tricaine methane sulphonate (MS 222) as a ¢sh anaesthetic, particularly in regard to reducing ¢sh stress. The biochemical blood pro¢les of perch Perca £uviatilis L. anaesthetized with either MS 222 (100 mg L À 1 ), clove oil (33 mg L À 1 ), 2-phenoxyethanol (0.40 mL L À 1 ) or Propiscin (1.0 mL L À 1 ), and a non-anaesthetized control group were compared. Biochemical pro¢les were determined from bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…Velisek and Svobodova (2004a) and Velisek et al (2005a) reported decreased AST activity in rainbow trout after clove oil and 2-phenoxyethanol anaesthesia. A similar change in LDH activity was reported by Velisek et al (2009) with clove oil anaesthesia in perch. Velisek et al (2011) reported increased activity of AST with clove oil and 2-phenoxyethanol anaesthesia in rainbow trout.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Velisek and Svobodova (2004a) and Velisek et al (2005a) reported decreased AST activity in rainbow trout after clove oil and 2-phenoxyethanol anaesthesia. A similar change in LDH activity was reported by Velisek et al (2009) with clove oil anaesthesia in perch. Velisek et al (2011) reported increased activity of AST with clove oil and 2-phenoxyethanol anaesthesia in rainbow trout.…”
Section: Discussionsupporting
confidence: 87%
“…Gomulka et al (2008) also reported decreased ammonia levels in Siberian sturgeon (Acipenser baerii) after eugenol (0.075 ml/l) and MS 222 (125 mg/l) anaesthesia. No changes in the levels of ammonia in rainbow trout, carp, European catfish, or perch following clove oil (30 mg/l) and 2-phenoxyethanol (0.30 ml/l) anaesthesia were observed by Velisek and Svobodova (2004a), and Velisek et al (2005bVelisek et al ( , 2007Velisek et al ( , 2009). Our differing results may be associated with the concentrations of the tested substances and the fish species used.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations